Kebaya janggan and Emotional Narrative: Sanggit Reinterpretation of Traditional Costume in Gadis Kretek - Aji, Fajar; Sugihartono, Ranang Agung (Institut Seni Indonesia Denpasar, 2025)
Film costumes shape and support the characters portrayed and play a crucial role in building cultural meanings and symbols for the characters and the film. Dasiyah’s costume in the original series Gadis Kretek is particularly intriguing for study due to its unique traditional kebaya, distinct from the other characters, and its distinctive use of form and color. This research aims to analyze the traditional kebaya worn by Dasiyah in the original series Gadis Kretek. This study employs a qualitative method with an intrinsic case study approach. Data were obtained from the original series Gadis Kretek and literature relevant to the research topic. Data collection was conducted through observation and literature review. Interpretative analysis utilizing the concept of sanggit is applied to examine the traditional kebaya worn by Dasiyah. The findings indicate that Kebaya janggan and the colors chosen can support and depict Dasiyah’s emotional state and the shifts in her emotions. The reinterpretation of Kebaya janggan through the sanggit concept demonstrates how traditional art values can be adapted with a modern touch, creating new meanings relevant to storytelling. The costume Dasiyah wore in Gadis Kretek also serves to reintroduce Kebaya janggan as one of Indonesia’s traditional kebayas to a broader audience, particularly the younger generation.